Extractors with vibratory mixing devices and prospects of their use in the food industry - Zavialov, Volodymyr; Bodrov, Viktor; Zaporozhets, Yuliia; Mysiura, Taras; Popova, Nataliia; Dekanskiy, Vadim (My University, 2012)
The low efficiency of the existing technologies for the extraction of desired components from vegetable raw materials with a high degree of milling is due to the imperfection of extraction equipment. Though the designs of modern periodic and continuous extractors are fairly diversified, there exist common disadvantages caused by the insignificant porosity of fine-fraction vegetable raw materials or the mass prepared from them for counterflow continuous extraction, their poor transportability, densification, and, as a result, the low permeability for the extractant. It has been established that vibratory extractors are most promising in this respect. In the present work, we present results of investigations of the intensifying action of low-frequency mechanical vibrations on the extraction process of desired components from vegetable raw materials under conditions of continuous vibration extraction. For industry, we propose a new design of a periodical and a continuous apparatus with vibratory mixing devices.
Keywords: vibratory extraction; intensification mass transfer; vegetable raw material; hydrodynamic flow; віброекстрактор; інтенсифікація масообміну; рослинна сировина; гідродинамічний потік; кафедра експертизи харчових продуктів; кафедра процесів і апаратів харчових виробництв